math

posted by .

multiply and simplify
36b^2/5b^2-20b+20*5b-10/6b.

  • math -

    Looks like
    (36b^2) / (5b^2 - 20b + 20) * (5b-10)/6b

    =36b^2/5(b-2)(b-2) * 5(b-2)/6b

    = 5*36b^2(b-2) / 5*6b(b-2)(b-2)

    = 6b/(b-2)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math

    please help me simplify this exponent 24^-1a^-3/6^-2b^-2 Basically it's this right?
  2. math

    how do i do x2+12x+32 x2+12x = 14x+32 subtract 14x from each side 14x=32 divide by 2 7x=16 x=16/7, which is 2 and 2/7 ok maybe you typed that question wrong?
  3. Algebra

    Solve S=a/(1-r) for r S = a/(1-r) Multiply both sides by 1-r S*(1-r) = [(1-r)*a]/(1-r) Simplify S*(1-r) = a Multiply terms on the left. S - S*r = a Subtract S from both sides. S-S*r - S = a - S Simplify -S*r = a - S Multiply both sides …
  4. someone help

    my post is still on this page as algebra, could someone elaborate on what bobpursley tried to help me with. See your original post. I am guessing you are referring to your question 5)Simplify:(5x-4)^2 and your answer= 25x^2 - 16 (5x-4)^2 …
  5. math

    Can someone help me with this problem? multiply and simplify 4 1/5 x 10/21 x 9/20. I know after you simplify 4 1/5 it will be 21/5. What is the next step.
  6. Math

    In this problem: 5/12b + 15/36b^2 First I made a common denominator: 15b/36b^2 + 15/36b^2 Then I simplified the first fraction: 5/12b + 15/36b^2 Can I simplify the second fraction by 3b?
  7. Algebra (check my answers)

    Please check these answers. Multiply -7(2a2 -4) = -14a2 + 28 Multiply 0.5(a + b -5) = 0.5a + 0.5b - 2.5 Factor bx - by + bz = b(x - y + z) Combine like terms (simplify) 12x + 4 - 11y - 6x - 9 - y = 6x - 12y - 5 Evaluate the expression …
  8. Algebra

    Can you please check my work? You have helped other students I know. Thank you:) Multiply -7(2a2 -4) = -14a2 + 28 Multiply 0.5(a + b -5) = 0.5a + 0.5b - 2.5 Factor bx - by + bz = b(x - y + z) Combine like terms (simplify) 12x + 4 -
  9. Math

    Multiply and Simplify: (a^x-a^(-x))^3 =(a^x-a^(-x))(a^x-a^(-x))(a^x-a^(-x)) =(a^x-a^(-x))(a^2x-a^0-a^0+a^(-2x)) =(a^x-a^(-x))(a^2x-2+a^(-2x)) =a^3x-2a^x+a^(-x)-a^x+2a^(-x)-a^(-3x) =a^3x-3a^x+3a^(-x)-a^(-3x) =?
  10. Math

    simplify the complex fraction 4/x+5 +2 _________ 14/x+5 -2 Once i multiply by the LCD i get 4+2(x+5)/14-2(x+5) however i can't see what i can do next to simplify can you explain.

More Similar Questions